To be Young! : Youth and the Future. Proceedings of the Conference “To be Young! Youth and the Future”, 6–8 June 2012, Turku, Finland - Jentl, Nina (ed.); Kaskinen, Juha (ed.) (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2019)
What does it mean to be young today and what will it mean in the coming years in this rapidly changing world? What the future of youth could be and look like? The aim of the “To be Young” conference in July 2012 was to perceive and create futures through the eyes of today’s youth, adults and decision makers for the young people of the future. The course of a youth’s life, both today and toward the future covers an entire spectrum of reality. Focusing on faith in young people, their ability and determination to build an inevitably different and in many ways and hopefully improved world for us all to live in was the focal point of this conference. This book collects some of the presentations and papers presented in the conference. Articles selected in this book cover several approaches of youth research. Topics include politics, education, gender questions, futures methodologies, young immigrants just to mention a few. We thank the authors and referees for their work. The conference was organized in association with the Finland Futures Academy and the Finnish Youth Research Network. The “To Be Young” conference marked Finland Futures Research Centre’s 14th Annual International Conference and its 20th Anniversary celebrating twenty years of academic research, education and development work.